THE ANALYSIS OF COVEY'S THE SEVEN HABITS OF mGHLY EFFECTIVE TEENS TRANSLATION VERSION - Marcella Rahayu; Emilia Ninik (Soegijapranata Catholic University, 2008)
Many translation books have undergone the process of translation, but some o/them contain problems of translatlon, which may lead to the spread o/inaccurate in formation. The problema may occur because the translation works contain distortion in it. The kinds of distortion itself vary in types. Therefore, In this study the writer explores the translation of Covey's Seven Habits for Highly Effective to find what kinds of distortlons, which the bookhos. The writer tries to classify the weak points In the translation version. The result of this analysis shows that there are six types of distortions found intranslation version. They are the distortion 0/ idiom, paraphrase, diction, under translation, over translation and mistranslation.